Purchasing Decision Model, Product Quality And Service Quality On Consumer Satisfaction On The Shopee Application Marketplace In Jember Regency - Angga Ade Permana Angga; Wasana Sinrungtam; Ihrom Caesar Ananta Putra; Abdul Wahid; Zainul Hasan (LPPM Institut Teknologi dan Sains Mandala, 2024)
Previous research is the most important thing in a research or scientific article. Previous research is useful for strengthening theories and phenomena that influence variables. This article reviews the factors that influence Product Quality and Service Quality on Purchasing Decisions and Consumer Satisfaction, a Marketing Management Literature Study. The purpose of writing this marketing management literature review article is to build a hypothesis that can be used in further research. The results of this library research are: 1) The Influence of Product Quality on Consumer Satisfaction; 2) The Influence of Service Quality on Consumer Satisfaction; 3) The Influence of Product Quality on Consumer Satisfaction; 4) The Influence of Service Quality on Consumer Satisfaction; 5) The Influence of Consumer Satisfaction on Purchasing Decisions;